New horizons for nomads - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Living with uncertainty: new directions for pastoral development in Africa. I Scones (ed), IT Publications. 1995. 214 pp. CTA number 650. 20 credits points